Organizational value systems and firms’ competitive advantage in the Nigerian banking industry - Solomon, Ekevwo Avuerieroye (International research journal of management, IT and social sciences, 2021)
The study addressed organizational value and the Firm’s Competitive Advantage in Nigeria Banking Industry in a bid to establish the relevance and relationship with Two objectives and evaluate the effect of brand value and corporate reputation on the firm’s competitive advantage. Two objectives and research questions were used to establish the relationship. A sample size of 124 was used for the study. Findings revealed a significant relationship amongst the variables. It was recommended that organizations should uphold values by ensuring that, there is respect for the senior employees, and ensuring determining appropriate organizational capabilities.